Impact of Digital Transformation on Nepalese Stock Market - Sah, Kiran Kumari (Journal of Nepal Commerce Association, 2025)
The digital transformation of Nepal’s stock market has reshaped its operational framework by improving accessibility, efficiency, and transparency. This shift has been driven by the introduction of online trading platforms such as the NEPSE Online Trading System (NOTS) and the Central Depository System and Clearing Limited (CDSC). This study examines the effectiveness of online trading in Nepal’s share market, focusing on investor awareness, operational challenges, and managerial solutions. The findings reveal that online trading has enhanced market accessibility and efficiency, leading to increased trading volumes and greater investor participation. However, the system continues to face significant challenges, including technological limitations, server inefficiencies, outdated infrastructure, and unstable internet connectivity. Limited digital literacy and inadequate investor education programs further restrict the effective use of online trading platforms. Moreover, regulatory gaps and weak cybersecurity measures undermine system reliability and investor trust. Despite growing adoption, many investors remain unaware of the full potential of digital trading. To address these issues, the study recommends upgrading technological infrastructure, strengthening regulatory and cybersecurity frameworks, and expanding investor education initiatives. The adoption of advanced technologies such as artificial intelligence and blockchain could further enhance security, transparency, and operational efficiency, enabling Nepal’s stock market to align with global financial standards.